INVESTIGETING OF DISTRESS AND ALEXITHYMIA IN PATIENTS WITH HEMATOLOGICAL CANCER - Didem Ayhan; Neşe Mercan; Reyhan Doğan; Çiğdem Yüksel (İstanbul Tıp Fakültesi Dergisi)
Objective: This study aimed to examine the levels of distress and alexithymia and the relationship between these two variables in individuals diagnosed with hematological cancer. Material and Method: This descriptive study was conducted between February and June 2018 with 135 individuals between the ages of 18 and 65 who were diagnosed with hematological cancer, who were undergoing inpatient and outpatient treatment in the hematology clinic of a training and research hospital, and who agreed to participate in the study. The data of the study were collected by introductory information form in line with the James Supportıve Care Screenıng and Toronto Alexithymia Scale. Results: In this study, the mean score of James Supportıve Care Screenıng was 50.2±21.2 and the mean score of the Toronto Alexithymia Scale was found to be 52.3±10.2. As a result of the correlation analysis, a moderate, positively significant correlation was found between the distress and alexithymia levels of individuals diagnosed with hematological cancer (r=0.412; p<0.001). Conclusion: This study concluded that alexithymic features could be observed in individuals diagnosed with hematological cancer as their distress levels increased. According to these results, it is suggested that healthcare professionals should support patients and intervene with regard to coping with stress, recognizing and expressing their feelings at the health service delivery.